2020
DOI: 10.30865/mib.v4i1.1652
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Algoritma C4.5 Untuk Prediksi Loyalitas Nasabah PT Erdika Elit Jakarta

Abstract: C4.5 algorithm is a decision tree algorithm group. This algorithm has input in the form of training samples and samples. While samples are data fields which we will use as parameters in classifying data. From the variable transaction frequency the company can see which customers are loyal to the company based on historical customer transaction data, but there are still some variables that make customers loyal to the company. These variables are age, customer gender, company sales gender, educational background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
3
0
7
Order By: Relevance
“…The author uses the C 4.5 algorithm on the basis of some literature from previous research from Teguh Budi Santoso with the title "Analisa Dan Penerapan Metode C4.5 Untuk Prediksi Loyalitas Pelanggan" with the results showing that classification with the C4.5 algorithm gets an accuracy of up to 97.5%, which means that the exact C4.5 algorithm is used to calculate the level of customer loyalty [1]. The second study entitled "Penerapan Algoritma C4.5 Untuk Prediksi Loyalitas Nasabah PT Erdika Elit Jakarta" by Khotibul Umam, based on the decision tree that has been made the attribute that has the most influence on customer loyalty is educational background because it has the highest gain value, namely 1.545292721 and as the root of the decision tree while the gender of the customer does not have much effect on customer loyalty because it is always at the last node with a gain value of 0.623919119 [2]. The third study entitled "Penerapan algortima c4.5 untuk penentuan kelayakan kredit" by Siti Nur Khasanah, Based on the results of the application of the C4.5 classifier algorithm, it can be concluded that to determine credit worthiness whether a prospective customer will become a customer with smooth or problematic payments using the C4.5 algorithm classifier and the accuracy of the C4.…”
Section: Methodsmentioning
confidence: 99%
“…The author uses the C 4.5 algorithm on the basis of some literature from previous research from Teguh Budi Santoso with the title "Analisa Dan Penerapan Metode C4.5 Untuk Prediksi Loyalitas Pelanggan" with the results showing that classification with the C4.5 algorithm gets an accuracy of up to 97.5%, which means that the exact C4.5 algorithm is used to calculate the level of customer loyalty [1]. The second study entitled "Penerapan Algoritma C4.5 Untuk Prediksi Loyalitas Nasabah PT Erdika Elit Jakarta" by Khotibul Umam, based on the decision tree that has been made the attribute that has the most influence on customer loyalty is educational background because it has the highest gain value, namely 1.545292721 and as the root of the decision tree while the gender of the customer does not have much effect on customer loyalty because it is always at the last node with a gain value of 0.623919119 [2]. The third study entitled "Penerapan algortima c4.5 untuk penentuan kelayakan kredit" by Siti Nur Khasanah, Based on the results of the application of the C4.5 classifier algorithm, it can be concluded that to determine credit worthiness whether a prospective customer will become a customer with smooth or problematic payments using the C4.5 algorithm classifier and the accuracy of the C4.…”
Section: Methodsmentioning
confidence: 99%
“…Algoritma C4.5 memiliki ide dasar untuk membentuk pohon keputusan. Pohon keputusan termasuk dalam klasifikasi dan prediksi terkenal karena relatif mudah dipahami dengan bahasa alami sehingga dapat diinterpretasikan dengan cepat [17].…”
Section: Pendahuluanunclassified
“…Algoritma ini mempunyai input berupa training samples dan samples. Sedangkan samples merupakan field-field data yang nantinya akan kita gunakan sebagai parameter dalam melakukan klasifikasi data [5]. Salah satu algoritma yang dipakai dalam data mining adalah algoritma C4.5 [6].…”
Section: Pendahuluanunclassified